The European debt crisis : The Greek case - Sēmitēs, Kōstas (Book collections on Project MUSE., 2014)
In this book, former Greek Prime Minister Costas Simitis examines the European debt crisis with particular reference to the case of Greece. Greece was the first Eurozone country to face an enormous deficit, which reached 15% of GDP in 2009. As the Greek crisis unfolded, other Eurozone countries displayed identical symptoms, albeit in varying degrees of severity. From a strictly Greek predicament the debt crisis quickly turned into a problem for the European Union as a whole. This first English language translation investigates the causes of this spillover and chronicles the policy responses to combat it. It also discusses Greece's troubled political economy, the country's difficulties in adjusting to the demands of its creditors and the vehement social and political reactions to the policy of austerity. The central argument of the book is that the principal cause of the European's problems was, and still remains, the indecisiveness of European elites to tackle its underlying deficiencies. Leading Eurozone countries have been unwilling to commit to a common long-term plan which could deal convincingly with complex and inter-related problems affecting both its 'core' and its 'periphery'. The guiding principle of policy responses thus far has been the pursuit of permanent fiscal discipline. Yet fiscal discipline alone would not provide the long-term solutions required; a steady course towards economic governance and political unification is necessary. Through his comprehensive and authoritative analysis, Simitis provides valuable insights into the crucial interconnection between Greece's own economic troubles and the wider European search for macroeconomic stability and sustainable economic growth. As such, the book appeals well beyond those with a narrow academic interest in Greece. This is very much a discussion about the future of the Eurozone and the European Union as a whole.